Defects, Diffusion, and Dopants in Li2Ti6O13: Atomistic Simulation Study - Kuganathan, N.; Sashikesh, G.; Chroneos, A. (MDPI, 2019)
In this study, force field-based simulations are employed to examine the defects in Li-ion diffusion pathways together with activation energies and a solution of dopants in Li2Ti6O13. The lowest defect energy process is found to be the Li Frenkel (0.66 eV/defect), inferring that this defect process is most likely to occur. This study further identifies that cation exchange (Li–Ti) disorder is the second lowest defect energy process. Long-range diffusion of Li-ion is observed in the bc-plane with activation energy of 0.25 eV, inferring that Li ions move fast in this material. The most promising trivalent dopant at the Ti site is Co3+, which would create more Li interstitials in the lattice required for high capacity. The favorable isovalent dopant is the Ge4+ at the Ti site, which may alter the mechanical property of this material. The electronic structures of the favorable dopants are analyzed using density functional theory (DFT) calculations.
Keywords: Li2Ti6O13; Defects; Li-ion diffusion; Dopants; Atomistic simulation; DFT